Interaction between Notch and Hif-alpha in development and survival of Drosophila blood cells. - Mukherjee, T.; Kim, W.S.; Mandal, L.; Banerjee, U. (Science, 2011)
A blood cell type termed crystal cell in Drosophila functions in clotting and wound healing and requires Notch for specification and maintenance. We report that crystal cells express elevated levels of Sima protein orthologous to mammalian hypoxia-inducible factor-? (Hif-?) even under conditions of normal oxygen availability. In these platelet-like crystal cells, Sima activates full-length Notch receptor signaling via a noncanonical, ligand-independent mechanism that promotes hemocyte survival during both normal hematopoietic development and hypoxic stress. This interaction initiates in early endosomes, is independent of Hif-? (?ang? in Drosophila), and does not activate hypoxia response targets. Studies in vertebrate myeloid cells have shown a similar up-regulation of Hif-? protein in well-oxygenated environments. This study provides a mechanistic paradigm for Hif-?/Notch interaction that may be conserved in mammals.